Aplikasi RPG Berbasiskan Teknologi Andengine pada Perangkat Mobile Android Gingerbread - Budi Yulianto; Andy Budy Pratama; Hutomo Widjaja (ComTech: Computer, Mathematics and Engineering Applications, 2012)
This article presents an application development of a Tactical Role-Playing Game based on AndEngine on an Android Gingerbread mobile device. The goals of the research are designing an entertaining application that implements artificial intelligence and AndEngine technology as well as presenting Indonesian cultures. The output of the research is a 2-dimension-based Tactical Role-Playing Game application implemented on Android Gingerbread mobile device and a game engine for creating items and skills of the characters for the game. On the application development phase, the research uses literature study, user requirement analysis, and similar game analysis. The research showed that the game application is developed using 2-dimension perception implementing artificial intelligence and AndEngine technology for having interesting control and appearance for users. In addition, it motivates other programmers for developing other game that presents Indonesian cultures, and uses conditional framerate for reducing battery usage on mobile device.